Bleeding risks for uncharacterized platelet function disorders. Issue 5 (30th May 2020) - Brunet, Justin; Badin, Matthew; Chong, Michael; Iyer, Janaki; Tasneem, Subia; Graf, Lucas; Rivard, Georges E.; Paterson, Andrew D.; Pare, Guillaume; Hayward, Catherine P. M.
Abstract: Background: The bleeding risks for nonsyndromic platelet function disorders (PFDs) that impair aggregation responses and/or cause dense granule deficiency (DGD) are uncertain. Objectives: Our goal was to quantify bleeding risks for a cohort of consecutive cases with uncharacterized PFD. Methods: Sequential cases with uncharacterized PFDs that had reduced maximal aggregation (MA) with multiple agonists and/or nonsyndromic DGD were invited to participate along with additional family members to reduce bias. Index cases were further evaluated by exome sequencing, with analysis of RUNX1 ‐dependent genes for cases with RUNX1 sequence variants. Bleeding assessment tools were used to estimate bleeding scores, with bleeding risks estimated as odds ratios (ORs) relative to general population controls. Relationships between symptoms and laboratory findings were also explored. Results: Participants with uncharacterized PFD (n = 37; 23 index cases) had impaired aggregation function (70%), nonsyndromic DGD (19%) or both (11%), unlike unaffected relatives. Probable pathogenic RUNX1 variants were found in 2 (9%) index cases/families, whereas others had PFD of unknown cause. Participants with PFD had increased bleeding scores compared to unaffected family members and general population controls, and increased risks for mucocutaneous (OR, 4‐207) and challenge‐related bleeding (OR, 12‐43), and for receiving transfusions for bleeding (OR, 100). Reduced MA with collagen was associated with wound healing problems and bruising, and more severe DGD was associated with surgical bleeding ( P  < .04). Conclusions: PFDs that impair MA and/or cause nonsyndromic DGD have significantly increased bleeding risks, and some symptoms are more common in those with more severe DGD or impaired collagen aggregation.